Contribution of Sufism to the development of moderate Islam in Nusantara - Anshori, M. Afif; Prasojo, Zaenuddin Hudi; Muhtifah, Lailial (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article analyzes the relationship between Sufism (mystical Islam) and the making of moderate Islam in Nusantara, a region that historically has been covered by various Muslim-majority populations in Southeast Asia, especially Indonesia. This focus is important for two reasons. First, Islam was first introduced to this region through the hands of Sufi preachers when Sufism was the the-dominant feature of Islam. Second, Islam has been practiced peacefully in this region for centuries through an adaptation with mystical practices of the local beliefs. Thus, the main question of this article is aimed at exploring the ways in which Sufism has contributed to the development of moderate Islam in Nusantara. In doing so, two different approaches are employed: the orthopraxic and historical approach and the phenomenological approach. While the former is especially employed to examine the historical introduction of Sufism into Nusantara, the latter is to analyze the essential teachings of Sufism, which are deemed flexible and inclusive towards cultural diversity. This study concludes that the development of moderate Islam in Nusantara cannot be separated from the century-long contribution of Sufism, the implication of which has created fundamental structures for harmonization of religious lives in Nusantara.